Cardiotoxicity in autologous haematopoietic stem cell transplantation for systemic sclerosis. Issue 2 (June 2023) - Penglase, Ross; Girgis, Laila; Englert, Helen; Brennan, Xavier; Jabbour, Andrew; Kotlyar, Eugene; Ma, David; Moore, John
Autologous haematopoietic stem cell transplantation is now well-established as an effective treatment for severe systemic sclerosis with clear demonstration of favourable end-organ and survival outcomes. Treatment-related cardiotoxicity remains the predominant safety concern and contraindicates autologous haematopoietic stem cell transplantation in patients with severe cardiopulmonary disease. In this review, we describe the cardiovascular outcomes of autologous haematopoietic stem cell transplantation recipients, discuss the potential mechanisms of cardiotoxicity and propose future mitigating strategies.